How personality traits influences quality of software developed by students - Barroso, Anderson S.; Prado, Kleber H. de J.; Soares, Michel S.; do Nascimento, Rogerio P. C. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
The activity of analyzing personality of software developers has been a topic discussed by many researchers over the past few years. However, their relation to software metrics has hardly been mentioned in the literature. This work aims to identify the influence of human personality on quality of software products. At first, a psychological test was performed using the MBTI model for a set of academy students and, subsequently, CK metrics were applied to individual software developed by members of the same group. As a result, it was evidenced, through statistical analysis, that the Response For a Classe(RFC) and Weighted Methods Per Class (WMC) metric, do not have a significant relationship with MBTI types. In another analysis, taking into account ideal average values for each CK metric, it was evidenced that Depth of Inheritance(DIT) metric have a significant relationship with MBTI types. Therefore, additional studies are needed to determine any deeper connection between personality and software quality.